2022
DOI: 10.1111/psyp.14206
|View full text |Cite
|
Sign up to set email alerts
|

Neural response to social but not monetary reward predicts increases in depressive symptoms during the COVID‐19 pandemic

Abstract: The prevalence of depressive symptoms has increased during the COVID‐19 pandemic, especially among those with greater pandemic‐related stress exposure; however, not all individuals exposed to pandemic stress will develop depression. Determining which individuals are vulnerable to depressive symptoms as a result of this stress could lead to an improved understanding of the etiology of depression. This study sought to determine whether neural sensitivity to monetary and/or social reward prospectively predicts de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Using multilevel models, we evaluated whether neural response to social or monetary reward predicted increases in depressive symptoms during the pandemic, again adjusting for baseline symptoms. We found that blunted neural response to social, but not monetary, reward predicted increased symptoms of depression during the early months of the pandemic (Freeman, Panier, et al, 2022), over and above variance accounted for by earlier self‐reported symptoms of symptoms of depression.…”
Section: Understanding Sources Of Variation In the Lpp And Rewpmentioning
confidence: 73%
See 2 more Smart Citations
“…Using multilevel models, we evaluated whether neural response to social or monetary reward predicted increases in depressive symptoms during the pandemic, again adjusting for baseline symptoms. We found that blunted neural response to social, but not monetary, reward predicted increased symptoms of depression during the early months of the pandemic (Freeman, Panier, et al, 2022), over and above variance accounted for by earlier self‐reported symptoms of symptoms of depression.…”
Section: Understanding Sources Of Variation In the Lpp And Rewpmentioning
confidence: 73%
“…Since the World Health Organization declared COVID‐19 an international pandemic on March 11th, 2020, much of the global population has undergone a sustained and uncontrollable stressor, though it must be acknowledged that stressors associated with the pandemic have been unevenly distributed across the population (e.g., Patel et al, 2020). The pandemic, now in its third year, has already had a profound impact on morbidity, mortality, social connection, and the global economy, and emerging evidence further demonstrates that stress related to the pandemic is predicting increases in depression symptoms, especially for women and girls (e.g., Freeman, Panier, et al, 2022; Hawes et al, 2021; Kujawa, Green, et al, 2020; Venanzi et al, 2022). My lab also wanted to see whether the pandemic has had an effect on neural responses to rewards.…”
Section: Understanding Sources Of Variation In the Lpp And Rewpmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, subclinical depressive symptoms were linked to reduced time-frequency delta power to social rewards ( Jin et al, 2019 ). Additionally, other studies indicated a smaller RewP to social acceptance in individuals with depression ( Kujawa et al, 2017 ; Distefano et al, 2018 ) and those at risk for the disorder ( Freeman et al, 2022a , b ).…”
Section: The Systems For Social Processesmentioning
confidence: 91%
“…Although preclinical work has consistently demonstrated that exposure to chronic stressors leads to impairment in dopamine signaling and reward responsiveness ( 13 , 21 , 22 , 23 ), results in humans have been more mixed. Though some studies have found that real-world stress exposure is associated with blunted reward response ( 24 , 25 , 26 , 27 , 28 ), others have found evidence of heightened reward sensitivity ( 18 ) or no association ( 27 , 28 , 29 ). This may depend on the type or severity of the stressor ( 18 ).…”
Section: Introductionmentioning
confidence: 99%